SINERGY OF DESA PAKRAMAN INTARAN AND ADMINISTRATIVE VILLAGE OF SANUR IN STRUCTURING THE IMMIGRANTS - Ni Luh Gede Yogi Arthani; Ni Putu Noni Suharyanti (Fakultas Hukum, Universitas Warmadewa, 2018)
Bali as one of the target areas of urbanization and mobilization is inseparable to the issues of immigrants. Sanur area, particularly the one that is known as a tourist area, has been most the target of the visits of immigrants seeking to improve the economy. Sanur Desa Pakraman Intaran of Denpasar has undergone transformation from a fishing village into a village that relies on tourism sector. Ideally, the immigrants or called as tamiu are obliged to report themselves to the head of the neighborhood or local prajuru adat/banjar for the creation of an orderly administration. However, in practice there are immigrants who have not cared to work on the rules. To overcome the problem, it is necessary to the efforts in the form of structuring the immigrants. Structuring the immigrants necessarily requires synergy between the village of service with pakraman in order to create the same understanding, vision and mission in order to control the immigrants.